PEMBERIAN HAK ATAS TANAH DI KAWASAN LINDUNG (SEMPADAN PANTAI DAN PULAU-PULAU KECIL) DITINJAU DARI ASAS KEMANFAATAN DAN KEPASTIAN HUKUM - Hariri, Ihwanun Mudhofir (Jurnal HUKUM BISNIS, 2024)
ABSTRACT: The birth of the Agrarian Law of 1960 was the beginning of the implementation of positive laws on land in Indonesia. However, in the Agrarian Principles Law has not fully regulated the right of coastal and small islands, some people even say that the coastal boundary is not an object in UUPA. This polemic is increasing in line with the status of Indonesia which adopts as an archipelago country, so the coastline and also the small islands in Indonesia also need a clear arrangement. Since the enactment of Government Regulation No. 16 of 2004 on Land Settlement of coastal boundaries and small islands that are generally included in protected areas can be given Land Rights except in forest areas, this is further strengthened by Law Number 1 of 2014 and also detailed Regulation Minister of ATR / KBPN No.17 of 2016. Thus paying attention to the rules and also on the basis of legal certainty and utility, the layout of land in coastal and small island border areas can be given rights to land. Even so far no court decision has revoked the certificate of land rights due to the judge's consideration of entering the coastal border. Keyword : agrary arrangement, coastal, island